2020
DOI: 10.1371/journal.pone.0239726
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sampling height on grass pollen concentrations in different urban environments in the Helsinki Metropolitan Area, Finland

Abstract: Introduction It is important to study potential differences in pollen concentrations between sampling heights because of diverse outdoor and indoor activity of humans (exposure) at different height levels in urban environments. Previous studies have investigated the effect of height on pollen concentrations based on just one or a few sampling points. We studied the effect of sampling height on grass pollen concentrations in several urban environments with different levels of urbanity. Methods This study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This is further corroborated by a study where it was demonstrated that there is no significant difference in Poaceae pollen concentrations between sampling at ground level in contrast to altitude of 16 m (Fernández-Rodríguez et al, 2014b). Due to this and the special circumstances a lower sampling height is fully justified as stated by Hugg et al (2020). The Corine Land Cover 2018 classifies the Lakeside area as a mix between non-irrigated arable land, pastures and complex cultivation patterns, with the surroundings (< 2 km) being mainly comprised of well-maintained grass areas, lakes, agricultural fields, and pastures.…”
Section: Locations and Pollen Monitoringmentioning
confidence: 52%
See 1 more Smart Citation
“…This is further corroborated by a study where it was demonstrated that there is no significant difference in Poaceae pollen concentrations between sampling at ground level in contrast to altitude of 16 m (Fernández-Rodríguez et al, 2014b). Due to this and the special circumstances a lower sampling height is fully justified as stated by Hugg et al (2020). The Corine Land Cover 2018 classifies the Lakeside area as a mix between non-irrigated arable land, pastures and complex cultivation patterns, with the surroundings (< 2 km) being mainly comprised of well-maintained grass areas, lakes, agricultural fields, and pastures.…”
Section: Locations and Pollen Monitoringmentioning
confidence: 52%
“…The height of the pollen sampler has been shown to play a role in the interpretation of the collected pollen analysis and results (Rojo et al, 2019). The reasoning is that sampling should be done elevated from the terrain, with a typical recommendation of about 10 m, while lower elevations can be justified based on the circumstance (Hugg et al, 2020). In our particular case the local circumstance is a flat area with much less atmospheric turbulence compared to an urban area.…”
Section: Locations and Pollen Monitoringmentioning
confidence: 98%
“…The studies were conducted outside Indonesia (Azmi et al 2015;Bisui et al 2019). Studies on pollen diversity collected by honey bees at different altitudes have been done outside Banyumas District, Central Java, Indonesia (Jayuli et al 2018;Pratama et al 2018;Hugg et al 2020). There was no study about pollen diversity collected by T. laeviceps from different altitudes in the Banyumas District, especially on pollen type and size.…”
Section: Introductionmentioning
confidence: 99%
“…Determining the potential and cultivation efforts of T. laeviceps bees is necessary to investigate the types of pollen collected by stingless bees at various altitudes (Hugg et al 2020). It is also essential to measure its diameter to determine the source of feed that supports productivity (Abbas and Sucianto 2020).…”
Section: Introductionmentioning
confidence: 99%